Strategi Mutu Pesantren dan Tantangan Dekadensi Moral di Tengah Geliat Artificial Intelligence - Sunardi, Sunardi; Utama, Wawan Kurnia; Munir, Muhammad (STAI Darul Kamal NW Kembang Kerang, 2024)
Technological advances have had a very significant impact on all aspects of human life. Starting from economic, political, social life, to the realm of education. Technological advances can make it easier to access global information. The existence of machines replaces the role of humans, causing the birth of an instant culture. Needs are served by smart machines and this causes a lack of human interaction. This literature research (library research) aims to explain the importance of moral, character and character education for students. However, humans interact with machines, learn via the internet, communicate via the internet and other artificial intelligence (Artificial Intelligence). However, moral and moral education must still be considered. The results of this research show that education must be directed at developing and maturing students' personalities. Therefore, the educational process does not only include the transfer of knowledge, but also the transfer of values ​​and skills, as well as the formation of morals and character (character building)